The influence of high and low glycaemic index meals on the glycaemic, metabolic and performance responses to running in type 1 diabetes. - Benjamin Gray (2011)
RATIONALE: Carbohydrate (CHO) ingestion is a recommended strategy to reduce the rislc of hypoglycaemia during and after exercise in people with type 1 diabetes (TIDM). Emerging research has shown that pre-exercise consumption of the low glycaemic index (GI) CHO isomaltulose increases blood glucose (BG) concentrations less and still protects against hypoglycaemia. However, glycaemic and performance benefits have been under-researched in TIDM following ingestion of CHO with differing GIs. This study compared the metabolic and performance responses to running following ingestion of a low- and high- GI CHO in TIDM. METHODS: With ethical approval, seven individuals (34+/-5 years, 70+/-2 kg, HbA1c 76.6+/-6.5 mmolmol-1) attended the laboratory twice following preliminary testing. Participants were provided with either 0.6 g kg-1 BM of either dextrose (DEX) or isomaltulose (ISO) immediately after a 50% reduced rapid-acting insulin dose. After 2-h rest participants completed a discontinuous incremental treadmill protocol (4-min running: 90 s rest at 31+/-1, 41 +/-2, 53+/-2, 69+/-3 and 80+/-2% VO2 PEAK) before a 10 min performance run. Blood samples were obtained throughout and analysed immediately for BG, lactate and other variables. Data are expressed as mean+/-SEM and analysed using repeated measures ANOVA with statistical significance (P<0.05). RESULTS: BG peak during the 2-h rest was lower after ingestion of ISO (ISO +5.6+/-0.4 vs. DEX +10.3+/-0.7 mmol L-1, P<0.05). BG reductions throughout the submaximal exercise were similar (ISO -1.9+/-0.5 vs. DEX -1.0+/-0.5 mmol L-1, P>0.05) as were changes following the performance bout (ISO +0.7+/-0.4 vs. DEX +0.7+/-0.3 mmol L-1, P>0.05). Lactate was higher in the 2-h rest period in ISO (P<0.05), although there were no differences once exercise began. Distance covered during the performance bout was comparable (ISO 1.14+/-0.09 vs. DEX 1.15+/-0.09 km, P>0.05). CONCLUSION: Pre-exercise consumption of ISO is an effective CHO for those exercising TIDM individuals wishing to improve glycaemic control without loss of exercise performance.